Security dimension of zakat: Strengthening Islamic education, mitigating social unrest, and promoting sustainable communities - Abdullahi, Nazifi Dahiru; Ibrahim, Ibrahim Aminu; Umar , Aliyu Salisu; Taufiq, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study investigates the multifaceted role of zakat in promoting not only poverty alleviation but also communal security, social stability, and sustainable community development. The research aims to expand the traditional understanding of zakat by highlighting its potential to address economic disparities and foster social cohesion. Employing a qualitative research design and secondary data analysis, the study systematically examines existing literature to assess the broader social and economic impacts of zakat. The findings demonstrate that effective zakat management can significantly mitigate social unrest by alleviating poverty, reducing unemployment, and addressing economic inequalities. Moreover, the study underscores the pivotal role of Islamic education in enhancing zakat's impact. By equipping recipients with financial literacy, entrepreneurial skills, and investment strategies, Islamic education enables sustainable resource management and economic empowerment. The research concludes that zakat, when combined with targeted educational interventions, can serve as a powerful tool for fostering financial security and communal peace. By integrating these approaches, zakat has the potential to become a catalyst for long-term social stability and the development of resilient, self-sustaining communities.